ANALISIS PROSEDUR PENGAJUAN DAN PEMBAYARAN KLAIM PADA PERUSAHAAN ASURANSI (Suatu Study Pada Asuransi Jiwa Bersama Bumiputera 1912 Ngawi) - Dewi, Ariani (Sekolah Tinggi Pariwisata AMPTA, 2008)
Insurance being known by person long since. Of year goes to insurance year go on amends a long with another service business developing. Carry on business insurance can amends because person progressively be conscious of jeopardy and perceiving needs to shift that jeopardy to on one’s side other one wants to take on by payment a number money as subtitution it. Insurance as business of service that offer jeopardy protection to its client apparently there are many experiences constraint. If doesn’t be noticed it will evoke problem in the short term and also long range.